2018
DOI: 10.1038/s41366-018-0151-9
|View full text |Cite
|
Sign up to set email alerts
|

Zinc alpha2 glycoprotein protects against obesity-induced hepatic steatosis

Abstract: Our results revealed that ZAG could protect against NAFLD by ameliorating hepatic steatosis, IR, and inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 51 publications
2
33
0
1
Order By: Relevance
“…The baseline characteristics of the cohort with normoalbuminuria (n=341) are shown in Table 1. The participants, of whom 52% were men, had a mean age of 57AE10 years and a median (IQR) diabetes duration of 8 (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) years. Baseline eGFR levels were progressively reduced as ZAG tertile increased.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The baseline characteristics of the cohort with normoalbuminuria (n=341) are shown in Table 1. The participants, of whom 52% were men, had a mean age of 57AE10 years and a median (IQR) diabetes duration of 8 (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) years. Baseline eGFR levels were progressively reduced as ZAG tertile increased.…”
Section: Resultsmentioning
confidence: 99%
“…The molecule functions as a lipid-mobilizing factor that stimulates lipolysis in adipocytes, contributing to weight loss and associated cancer cachexia [9]. Studies in humans and animal models have suggested a protective role of ZAG against obesity, insulin resistance, hepatic steatosis, and inflammation [10][11][12]. Contradictorily, ZAG protein expression was found to be upregulated in the white adipose tissue of people and mice with CKD [13].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, one study showed that the overexpression of ZAG alleviated HFD-induced IR and decreased the lipid contents of muscles in mice [22]. Another study showed that ZAG overexpression could protect against nonalcoholic fatty liver disease (NAFLD) in vivo or in vitro by ameliorating hepatic steatosis, IR, and inflammation [23]. Therefore, we speculated that decreased ZAG levels in obese and IR subjects potentially occur to offset IR-induced metabolic stress.…”
Section: Discussionmentioning
confidence: 97%
“…Insulin receptor substrate-1 (IRs-1) is a core factor in insulin signaling transduction. Research showed that phosphorylation of IRs-1 at Ser accounts for IR, while phosphorylation of IRs-1 at Tyr is required for responses of insulin stimulates (Bhattacharyya et al 2015;Xiao et al 2018) . In metabolic disorders, such as NAFLD and T2DM, impaired IRs-1 level was observed, for instance, lipid accumulation in the liver was closely associated with increased serine phosphorylation of IRs-1 (Araujo et al 2018;Dallak 2018;Dong et al 2019).…”
Section: Discussionmentioning
confidence: 99%